Система контроля параметров окружающей среды и разведки местности - Сухарев, Р. М.; Карнаушенко, В. П. (ХНУРЕ, 2018)
The remotely controlled system for penetrating into hard-to-reach or dangerous places for people and subsequent measurement of environmental parameters (temperature, humidity, pressure, vibration) and reconnaissance of the terrain has been developed.
Keywords: Система контроля параметров; разведка местности